Activated Microglia Induce Bone Marrow Mesenchymal Stem Cells to Produce Glial Cell-Derived Neurotrophic Factor and Protect Neurons Against Oxygen-Glucose Deprivation Injury - Lv, Bingke; Li, Feng; Fang, Jie; Xu, Limin; Sun, Chengmei; Han, Jianbang; Hua, Tian; Zhang, Zhongfei; Feng, Zhiming; Wang, Qinghua; Jiang, Xiaodan (Frontiers in Cellular Neuroscience, 2016)
In this study, we investigated interactions among microglia (MG), bone marrow mesenchymal stem cells (BMSCs) and neurons in cerebral ischemia and the potential mechanisms using an in vitro oxygen-glucose deprivation (OGD) model. Rat BMSCs were incubated with conditioned medium (CM) from in vitro cultures of OGD-activated rat MG and murine BV2 MG cells. Effects of glial cell-derived neurotrophic factor (GDNF) on rat neuron viability, apoptosis, lactate dehydrogenase (LDH) leakage and mitochondrial membrane potential (MMP) were analyzed in this model. OGD-activated MG promoted GDNF production by BMSCs (P < 0.01). TNFα, but not IL6 or IL1β, promoted GDNF production by BMSCs (P < 0.001). GDNF or CM pre-treated BMSCs elevated neuronal viability and suppressed apoptosis (P < 0.05 or P < 0.01); these effects were inhibited by the RET antibody. GDNF activated MEK/ERK and PI3K/AKT signaling but not JNK/c-JUN. Furthermore, GDNF upregulated B cell lymphoma 2 (BCL2) and heat shock 60 kDa protein 1 (HSP60) levels, suppressed LDH leakage, and promoted MMP. Thus, activated MG produce TNFα to stimulate GDNF production by BMSCs, which prevents and repairs OGD-induced neuronal injury, possibly via regulating MEK/ERK and PI3K/AKT signaling. These findings will facilitate the prevention and treatment of neuronal injury by cerebral ischemia.